Phosphorylation at Tyrosine 262 Promotes GADD34 Protein Turnover - Zhou, Wei (American Society for Biochemistry and Molecular Biology, 2013)
In mammalian cells, metabolic and environmental stress increases the phosphorylation of the eukaryotic translational initiation factor, eIF2α, and attenuates global protein synthesis. Subsequent transcriptional activation of GADD34 assembles an eIF2α phosphatase that feeds back to restore mRNA translation. Active proteasomal degradation of GADD34 protein then reestablishes the sensitivity of cells to subsequent bouts of stress. Mass spectrometry established GADD34 phosphorylation on multiple serines, threonines, and tyrosines. Phosphorylation at tyrosine 262 enhanced the rate of the GADD34 protein turnover. Substrate-trapping studies identified TC-PTP (PTPN2) as a potential GADD34 phosphatase, recognizing phosphotyrosine 262. Reduced GADD34 protein levels in TC-PTP-null MEFs following ER stress emphasized the importance of TC-PTP in determining the cellular levels of GADD34 protein. The susceptibility of TC-PTP-null MEFs to ER stress-induced apoptosis was significantly ameliorated by ectopic expression of GADD34. The data suggested that GADD34 phosphorylation on tyrosine 262 modulates endoplasmic reticulum stress signaling and cell fate.